Pengaruh Ketersediaan, Distribusi, dan Kualitas Produk Terhadap Kepuasan Konsumen AMDK Voca UNDIP - Huwaida, Rofifah Salma; Suwandi, Suwandi (Serat Acitya, 2025)
Bottled Drinking Water (AMDK) “VOCA” is produced by the Teaching Factory Water Treatment, Vocational School of Diponegoro University, to meet the hydration needs of the academic community. However, several issues have been identified, such as packaging defects, uneven product distribution, and stock shortages during peak demand, particularly at large-scale campus events. These issues may affect consumer satisfaction with the VOCA product. This study aims to analyze the influence of product availability, distribution, and product quality on consumer satisfaction. The research uses a quantitative approach with a survey method involving respondents who have consumed VOCA. The sampling technique applied was purposive sampling, and the data were analyzed using multiple linear regression. The results show that all three variables—product availability, distribution, and product quality—have a positive and significant effect on consumer satisfaction, both partially and simultaneously. Among them, product quality is the most dominant factor. These findings highlight the importance of consistently maintaining product quality, improving distribution systems, and ensuring stock availability to meet consumer expectations and enhance the competitiveness of VOCA on campus.